2014
DOI: 10.1007/s13277-014-2838-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein expression of glucose transporter 1 and glucose transporter 3 in human laryngeal cancer—the relationship with regulatory hypoxia-inducible factor-1α expression, tumor invasiveness, and patient prognosis

Abstract: Increased glucose uptake mediated by glucose transporters and reliance on glycolysis are common features of malignant cells. Hypoxia-inducible factor-1α supports the adaptation of hypoxic cells by inducing genes related to glucose metabolism. The contribution of glucose transporter (GLUT) and hypoxia-inducible factor-1α (HIF-1α) activity to tumor behavior and their prognostic value in head and neck cancers remains unclear. The aim of this study was to examine the predictive value of GLUT1, GLUT3, and HIF-1α me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…All DEGs were classified into GO and KEGG categories to provide an overview of their biological functions and associated biochemical pathways. Many studies have shown the expression of individual hypoxia-related genes in different cells (28)(29)(30). In the present study, our analysis indicated that the upregulated genes were highly enriched in ECM organization (GO:0030198), protein binding (GO:0005515), extra ventricular cardiac muscle cell differentiation (GO:0055012), diphosphotransferase activity (GO:0016778) and the cytoplasm (GO:0005737).…”
Section: Discussionsupporting
confidence: 49%
“…All DEGs were classified into GO and KEGG categories to provide an overview of their biological functions and associated biochemical pathways. Many studies have shown the expression of individual hypoxia-related genes in different cells (28)(29)(30). In the present study, our analysis indicated that the upregulated genes were highly enriched in ECM organization (GO:0030198), protein binding (GO:0005515), extra ventricular cardiac muscle cell differentiation (GO:0055012), diphosphotransferase activity (GO:0016778) and the cytoplasm (GO:0005737).…”
Section: Discussionsupporting
confidence: 49%
“…Intratumoral hypoxia is a common feature of solid malignancies, including LSCC. Indeed, HIF1a has been well studied in cancer progression and is implicated in the malignancy phenotype of LSCC [3738]. Phosphoinositide-3-kinase regulatory subunit 1(PIK3R1) binds, stabilizes and inhibits the PI3K p110 catalytic subunit [39].…”
Section: Discussionmentioning
confidence: 99%
“…Accepted standards for tumor staging and oncologic prognostication continue to be helpful in confronting these challenges and guiding decision making . However, in order to further individualize treatment selections that enhance survival and minimize morbidity, more sophisticated methods that successfully capitalize on emerging discoveries related to tumor biology/genomics and patient factors are mandatory . Treatment decision making is particularly complex for laryngeal cancer because of the various treatment options available and the differing short‐term and long‐term functional consequences that affect quality of life and survival.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, in order to further individualize treatment selections that enhance survival and minimize morbidity, more sophisticated methods that successfully capitalize on emerging discoveries related to tumor biology/genomics and patient factors are mandatory. 8,9 Treatment decision making is particularly complex for laryngeal cancer because of the various treatment options available and the differing short-term and long-term functional consequences that affect quality of life and survival. The management of laryngeal cancer has experienced substantial evolution, primarily driven by the implementation of chemotherapeutic modalities and novel organ-preservation strategies.…”
Section: Introductionmentioning
confidence: 99%